2022
DOI: 10.3390/antiox11091765
|View full text |Cite
|
Sign up to set email alerts
|

The Activation of Nrf2/HO-1 by 8-Epi-7-deoxyloganic Acid Attenuates Inflammatory Symptoms through the Suppression of the MAPK/NF-κB Signaling Cascade in In Vitro and In Vivo Models

Abstract: In this study, we examined the ameliorative effects of 8-epi-7-deoxyloganic acid (DLA), an iridoid glycoside, on oxidative stress and inflammation in both LPS-stimulated macrophages and mice with carrageenan-induced inflammation. DLA decreased oxidative stress through the up-regulation of heme oxygenase-1 (HO-1) via the activation of nuclear factor erythroid 2-related factor 2 (Nrf2), leading to the suppression of reactive oxygen species (ROS) and nitric oxide generation (NO). In addition, DLA inhibited the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Inflammation plays a key role in the occurrence and development of CRC 34 , 35 . Therefore, we determined the expression of the pro-inflammatory mediator, inducible nitric oxide synthase (iNOS), and the inflammatory gene-related transcription factor, NF-κB 36 38 . The expression of p-NF-κB p65 was decreased in the ALOX5 knockdown group compared to the control group ( Figure 3D ).…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation plays a key role in the occurrence and development of CRC 34 , 35 . Therefore, we determined the expression of the pro-inflammatory mediator, inducible nitric oxide synthase (iNOS), and the inflammatory gene-related transcription factor, NF-κB 36 38 . The expression of p-NF-κB p65 was decreased in the ALOX5 knockdown group compared to the control group ( Figure 3D ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the thermosensitive niobium carbide (Nb 2 C)-based hydrogel (Nb 2 C@Gel), which has antioxidant and antimicrobial activity, could promote wound healing by attenuating ROS levels [ 18 ]. A specific role of Nrf2 was highlighted in research by Simu et al, which indicated that oxidative stress could be decreased by activating Nrf2, as Nrf2 mediates ROS elimination and nitric oxide generation [ 19 ]. Therefore, based on these studies, it is reasonable that the Nrf2-related downstream genes, such as HO-1, could be upregulated by knocking down Keap1.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of garcinol on the production of pro-inflammatory molecules while an NF-kB inhibitor is present should also be validated in order to support whether garcinol can suppress the NF-kB signaling pathway. Moreover, the proteasome inhibitor should be used to confirm the effect of garcinol on the proteasomal breakdown pathway [ 59 ]. The proposed model of garcinol anti-inflammatory activity based on the results of this study is illustrated in Figure 8 .…”
Section: Discussionmentioning
confidence: 99%